Navigating The Development Of Halal Industry: Tracking Institutional Influences In The Indonesian Context - Mohammad, fadhel (ITB AAS INDONESIA Surakarta, 2024)
This research studies the development of the halal industry in Indonesia by highlighting the influence of institutional factors in halal certification. As a country with the largest Muslim population in the world, the demand for halal products is very high, making the halal industry has an important role in the national economy. The purpose of this study is to identify institutional factors that influence the growth and dynamics of the halal industry, including government regulations, the role of halal certification bodies, and support from religious and business organizations. The research method used is qualitative analysis, with secondary data collection from literature and industry reports as supporting analysis. The results show that strong and transparent government regulations, as well as close cooperation between certification bodies and industry players, are key factors in the development of the halal industry in Indonesia. In addition, the support and trust of Muslim consumers in halal-certified products also drives the growth of this industry. This study suggests improving inter-agency coordination and strengthening the regulatory framework to encourage sustainable growth of the halal industry in Indonesia.